Внутрішньовидова та міжвидова реакція альгологічно чистих культур синьозелених водоростей на зміни умов вирощування - Мушак, П.О. (Інститут ботаніки ім. М. Г. Холодного НАН України, 2007)
Изложены результаты исследований влияния углеродного питания и освещения на продуктивность синезеленых водорослей и накопление белка. Установлены некоторые отличия в их реакции на изменения условий выращивания, причем значительные отличия наблюдаются на уровне видов. Так, согласно нашим данным, под действием глюкозы более интенсивными являются рост и накопление белка у N. punctiforme 39 по сравнению с N. muscorum 81. Изменение условий культивирования водорослей в меньшей мере сказывается на уровне штаммов N. punctiforme 38 і N. punctiforme 39. Интенсивность усвоения глюкозы в темноте практически идентична как на уровне вида, так и штаммов. Добавление диурона в питательную среду полностью угнетает ростовые процессы, наличие глюкозы в среде значительно ослабляет действие диурона. Также различна реакция исследованных водорослей на интенсивность и длительность освещения. Results of researches concerning the influence of carbon nutrition and lighting on the productivity of blue-green algae and protein accumulation have been presented in this article. It was determined some differences in reaction of these organisms on changes of growth conditions, moreover, significant differences were observed on the level of species. Thus, according to our data, more intensive growth and protein accumulation in N. punctiforme 39, than in N. muscorum 81 takes place under glucose action. Change of cultivation conditions of algae is manifested to a lesser degree on the level of strain of N. punctiforme 38 and N . punctiforme 39. The intensity of glucose assimilation in darkness takes place almost in the same degree both at the level of species and strain. The addition of diuron to the nutrition medium completely depresses of growth processes, the presence of glucose in medium significantly decreases the diuron action. The reaction of algae also investigated is different on the intensity and lighting duration.